THE FLOOD RISK STUDY OF ONGKAK DUMOGA RIVER IN KABUPATEN BOLAANG MONGONDOW - Endro Tomici Sukarno, David
Flood is a natural phenomenon that occurs when water stagnates in a location. The flooding that occurred in the Ongkak Dumoga Bolaang Mongondow Regency was due to the cross-sectional capacity of the river not being able to accommodate the flood discharge and causing the water to overflow during the rainy season. The purpose of this study was to calculate the design discharge using the HSS Snyder and HSS Nakayasu methods, to model inundation height, depth, and flood velocity using HEC-RAS 2D software, and to map flood risk using ARC-GIS software in the Ongkak Dumoga watershed. Both methods were calibrated using the Creager Method and obtained close results, namely the HSS Snyder Method. The results of the analysis of flood discharge using the HSS-Snyder method get a discharge of 1110.51 m/s at the 100 year return period, 992.73 m³/s at the 50 year return period, 887.22 m³/s at the 25 year return period. The results of the analysis of the level of flood risk based on the parameters of flood threat and vulnerability indicate that the level of flood risk at the study location along the 6km in the Ongkak Dumoga watershed is classified as a High Flood Risk Level dominated by Langagon II Village and Totabuan Village, which is 397 ha. Followed by the Moderate Flood Risk Level of 369 ha. And Low Flood Risk Level of 343 ha.